A Complicated Pregnancy in an Adult with HNF4A p.R63W-Associated Fanconi Syndrome. (26th December 2019) - Anyiam, Oluwaseun; Wallin, Elizabeth; Kaplan, Felicity; Lawrence, Christopher
Abstract : Renal Fanconi syndrome (RFS) is characterised by generalised dysfunction of the proximal renal tubules, resulting in excessive urinary loss of solutes, most notably bicarbonate, and type II (proximal) renal tubular acidosis. It is a rare condition, and literature around its management through pregnancy is limited. We present the management of a 37-year-old woman with RFS secondary to the HNF4A p.R63W mutation, through her third pregnancy. She presented at 28 + 5 weeks with dehydration, low serum bicarbonate, and profound metabolic acidosis. Daily infusions of sodium bicarbonate were necessary, and the requirements increased throughout the pregnancy. She also demonstrated both fasting hypoglycaemia and episodes of postprandial hyperglycaemia which required complex management. Due to concerns around fetal health, an elective caesarean section was performed at 34 weeks, delivering a healthy baby girl. This case highlights the potential complexity of pregnancy in patients with RFS and the need for a multidisciplinary approach to its management.